(3GdbGFO GdGLJeGYj (B/s - (3GdOHd, EHQGgje eMeO LGSes; (3eMeO, YHO GdQMef TQas ((3GdEeGQGJ GdYQHjI GdeJMOI (B:s (3OGQ cJGH ddfTQ hGdJhRjY,s, 2016)
(3jYJHQ cJGH (B"(3GdbGFO GdGLJeGYj(B" (3ddeDda (B"(3EHQGgje eMeO LGSe GdOHd(B" (3HeKGHI Odjd aj GdJOQjH GdEOGQj hGdbjGOj, hjQcR Ydi GdGgJeGe HGdTHGH hJhYjJge hJOQjHge ddJYGed eY GdJMOjGJ GdeMjWI Hge, ef NdGd Jecjfge hJYQjage HCOhGQge GdGLJeGYjI GdJj JUH aj eUdMI hWfge hCSQge heDSSGJge, hjSdW GdVhA Ydi YOO ef GdegGQGJ hGdbOQGJ GdJj JYed Ydi Jchjf GdUaGJ GdbjGOjI ddTHGH(B.s
(3GdeMJhjGJ (B: (3JegjO(B-(3GdHGH GdChd (B: (3GdbGFO hGdbjGOI (B: (3GdaUd GdChd (B: (3GdbGFO GdGLJeGYj(B-(3GdaUd GdKGfj (B: (3GdbjGOI(B-(3GdaUd GdKGdK (B: (3GdCfeGW hGdSdhc GdbjGOj(B-(3GdHGH GdKGfj (B: (3GdJWhY hGdGMJSGH (B: (3GdaUd GdChd (B: (3GdJWhY(B-(3GdaUd GdKGfj (B: (3GdGMJSGH(B-(3GdHGH GdKGdK (B: (3GdYQV hGdJbOje (B: (3GdaUd GdChd (B: (3egGQGJ GdYQV hGdEdbGA(B-(3GdaUd GdKGfj (B: (3NW SjQ GdeMGVQ GdfGLM(B. s
(3JUeje hENQGL (B: (3CSGeI CSYO GdaGQS(B.s
(3HHdjhLQGajI (B: (3UaMI (B234-239.s
Keywords: (3GdbjGOIs -- (3LhGfH GLJeGYjIs; (3GdSdhc GdGLJeGYjs